Ontology-services agent to help in the structural and semantic heterogeneity - Andreia Malucelli (2004)
In the Virtual Enterprises (VE) environment, interactions between distributed heterogeneous computing entities representing different enterprises, people and resources, take place. These interactions, in order to be both syntactic and semantic compatible, need to follow appropriate standards (ontologies) well understood by all the participants. Even for each domain ontology, people may store their data in different structures and use different terms to represent the same concept. This paper focuses on an effort to create an Ontology-Services Agent to monitor the communication acts taking place in a Multi-agent System. The Ontology-Services Agent provides help in solving the Structural and Semantic Heterogeneity problem, enabling appropriate conversations and making it possible meaningful agreements between agents representing different enterprises and resources in a VE environment.